Is there New Condylar Formation after Unilateral Partial Mandibular Condylectomy? (International Journal of Medical and Surgical Sciences, 2015)
Facial asymmetry related to unilateral condylar hyperplasia is one of the facial deformities diseases, usually treated with TMJ surgery. The aim of this review is to define if condylar reparation is possible after partial resection of the condylar head and establish the conditions. We realized a search in Pubmed Central, Science Citation Index, Elsevier Science Direct Complete, Highwire Press, Springer Standard Collection, to find the studies realized in condylar reparation after condylectomy in humans and animals. The results showed poor information for both, human and animal model research. The information shows that condylar reparation is possible after condyelectomy, demonstrating similar morphology with the normal non-operated condyles. Functional load, age and surgery presented relation with condylar reparation.
Keywords: Condylectomy; Condylar hyperplasia; Facial asymmetry